Strategi Pemberdayaan Masyarakat Petani Kopi Desa Sibio-bio Kecamatan Marancar Dalam Meningkatkan Kesejahteraan Petani - Aisyah Budi Harahap (Fakultas Dakwah dan Ilmu Komunikasi, 2022)
This study aims to analyze the coffee farmers empowerment strategy in increasing village income through increasing coffee production in Sibio-bio Village, Marancar District, South Tapanuli Regency. The method in this study uses a qualitative research approach with the source of the data obtained is the result of direct observation and interviews with coffee farmers in Sibio-bio village. The results showed that the factors for increasing crop yields came from: How the strategies were carried out in empowering farmers to increase crop yields, the driving factors for coffee farming, and the inhibiting factors for coffee farming.